Pathophysiology of Heart Disease: a collaborative project of medical students and faculty/ Leonard S. Lilly - Lilly, Leonard S. (Estados Unidos de América : Lippincott Williams & Wilkins, 2003)
A knowledge of normal cardiac structure and function is crucial to understanding diseases that afflict the heart.
1. Basic Cardiac Structure and Function 2. Hypertension
Incluye Indice
Col. Salud
Keywords: 1. CLINICAL ASPECTS OF CARDIAC 2. CARDIOVASCULAR DRUGS 3. ATHEROSCLEROSIS